PENGARUH KREDIBILITAS YOUTUBER RADITYA DIKA TERHADAP MINAT GENERASI Z BERINVESTASI DI PASAR MODAL - Muhammad Affan Inamullah (2023)
This study aims to analyze and see how far the influence of YouTuber Raditya Dika's credibility has on Generation Z's interest to invest in the capital market. This study uses the theory of source credibility. Raditya Dika's credibility is measured based on the dimensions of trustworthiness, expertise, and attractiveness. Meanwhile, interest in investing is measured based on cognitive, affective, and conative dimensions. The method used is descriptive quantitative using primary and secondary data sources. The sample used was 100 respondents with generation Z criteria who followed the Raditya Dika YouTube account and knew and obtained information regarding investment in the YouTube account. In analyzing the data, researchers conducted validity and reliability tests, classical assumption tests, correlation tests, simple linear regression tests, coefficient of determination tests, and hypothesis testing. The results of this study indicate that the credibility of YouTuber Raditya Dika has an influence on Generation Z's interest in investing in the capital market by 60%, while the remaining 40% is influenced by other factors. Generation Z agrees that Raditya Dika has a good reputation as an influencer by 80% and has public speaking skills by 86%. The influence by Raditya Dika's YouTube content makes Generation Z have an interest in investing by 55% and investing in the capital market by 49%. The results of this study also show that there is a very strong relationship between variables X and Y and is positive. It can be concluded that the credibility of YouTuber Raditya Dika has a significant effect on Generation Z's interest in investing in the capital market.